Presencia de lesiones en el entrenamiento físico mílitar. una experiencia de investigación en la escuela militar de cadetes general josé maría cordova (2019)
The military that is in the process of formation is subject to high physical, mental and psychological demands that are increased by the time of concentration, by the hours of training and the density of the activities. It is for the above, that the training process is similar to that of high achievements for its duration greater than six months consecutively and on a daily basis, in this way the military presents a greater risk to the appearance of injuries, which may lead to to slow recovery processes and generate in some cases the desertion of this. The objective of the investigation was to know the injuries resulting from the military physical training in the Military School of General Cadets José María Córdova. This study was of a quantitative type, descriptive in nature. A survey was designed to know the injuries resulting from military physical training. Within the results it was evident that many of the injuries presented are due to overtraining and overexertion on the part of the commanding officers or the cadets themselves, motivated by excelling, having better conditions within the School or by fulfilling extra orders than in their Most are physical exercises for actions against their regulation. It was determined that this is a population that is not generally taken into account in the area of physical activity and sports, as it is the force that protects the country and the context in which they must train and the consequences of this to go out to provide a service to the nation.